AN ANALYSIS OF REGIONAL IMBALANCES IN IRAN: A CASE STUDY OF NORTH COASTAL AREAS - Taghvaei, Masoud; Shafaghi, Sirous; Ghaderi, Mohammadreza (PLANNING MALAYSIA, 2017)
In countries such as Iran, which cover a large geographical area, the issue of inequality and regional differences provide a substantial challenge in the effort to achieve balanced development. In this study, data were collected using documentary and survey methods as well as Delphi techniques, and analysis was carried out by combining qualitative and quantitative models. In the second step of the Delphi technique, a study of the impact of the factors on each other, and on the regional inequalities of the North coastal area, was made using the crossimpact method. In the final step, the effective factors contributing to the inequalities of the North coastal region were studied using analytical techniques and MicMac software. After analyzing the impact rate of the effective factors on regional imbalances, the key factors were identified and, finally, solutions to reduce the regional imbalances of the North coastal area were proposed.